Breast cancer burden (1990–2040) in individuals aged 55 and above: a GBD 2021 analysis of global trends, sex-specific risk factors, and intervention impact - Shimao Jian; Wanmei Lin; Yuewen Tang; Guangyu Yao (Frontiers in Public Health)
BackgroundBreast cancer remains a leading cause of death among women, with incidence and mortality rates sharply increasing with age, particularly in individuals aged 55 and above. This study provides a comprehensive assessment of the global breast cancer burden in this high-risk demographic.MethodsUtilizing Global Burden of Disease (GBD) 2021 study data, we analyzed breast cancer incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for individuals aged 55 and older from 1990 to 2021. Temporal trends were quantified using age-standardized rates (ASRs) and Estimated Annual Percentage Changes (EAPCs). Population Attributable Fractions (PAFs) delineated sex-specific contributions of modifiable risk factors. A Bayesian age-period-cohort (BAPC) model projected the future burden to 2040, rigorously validated by sensitivity analysis. Crucially, an evidence-based scenario analysis was employed to model the potential impact of various public health interventions.ResultsGlobally, absolute breast cancer cases and deaths in the 55+ population significantly increased (1990–2021), despite a modest decline in the age-standardized mortality rate. Profound disparities emerged across Socio-Demographic Index (SDI) regions, with low-to-middle SDI regions experiencing sharp increases in incidence and mortality, contrasting with declining standardized mortality in high-SDI regions. Risk factor analysis revealed distinct sex-specific profiles: female DALY burden was predominantly driven by metabolic risks (e.g., high BMI), while male burden was overwhelmingly attributable to high alcohol consumption. Baseline projections to 2040 suggest rate stabilization; however, scenario analysis demonstrated high malleability: enhanced screening could avert millions of cases, whereas pessimistic scenarios (e.g., COVID-19 pandemic disruptions) could reverse current progress.ConclusionThe breast cancer burden in the aging population is substantial and increasingly concentrated in developing regions. The distinct risk profiles between sexes, combined with the profound potential of targeted interventions, underscore the urgent need for tailored, proactive, and resource-stratified public health strategies to mitigate the projected global burden.